Loose shell syndrome (LSS) of cultured Penaeus monodon - microbiological and histopathological investigations - Loka, Jayasree; Janakiram, P.; Geetha, G. K.; Sivaprasad, B.; Veerendra kumar, M. (Indian Journal of Fisheries, 2012)
Investigations were undertaken on loose shell syndrome (LSS) of cultured Penaeus monodon during the period 2009 - 2010. The infected shrimps were collected from culture ponds of east and west Godavari districts in Andhra Pradesh, India and were subjected to microbiological and histopathological studies. Four species of Vibrio were isolated from the diseased shrimps and were identified as V. harveyi, V. alginolyticus, V. metschnikovii and V. fluvialis based on morphological characteristics and biochemical tests. Histopathological studies revealed the presence of occlusion and inclusion bodies of monodon baculovirus (MBV), hepatopancreatic parvo-like virus (HPV), and white spot syndrome virus (WSSV) in hepatopancreatic and gill tissues. All the LSS affected shrimps collected during the present study were found infected with V. harveyi and concurrent infections of other Vibrio species were observed in 40% of the samples. Prevalence of infection with WSSV, MBV and HPV was less compared to Vibrio infections. Granuloma formation was observed in the affected tissues due to bacterial invasions. Multiple viral infections in association with Vibrio sp. were also observed in 2% of LSS affected shrimp.